Pengaruh Modifikasi Lembar KPSP Menggunakan Dart Game terhadap Kemampuan Balita di TK Al-Mujahidin - Harlinah Harlinah; Rizqi Kamalah (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Toddler period is an essential period in human life-cycle and requires a serious attention to the rapid growth and development process.  Nutritional status is internationally recognized as an indicator that influenced the growth and development of children. The most important monitoring in children’s development is during the first 3 years by using the Pre-Screening Developmental Questionnaire. Pre-Screening Developmental Questionnaire can be implemented in children up to the age of 6. PDQ can be used by midwife as a monitoring tool of children’s development. This study aims to determine the effect of modifying KPSP using dart games on toddlers' abilities. This research is a quasi-experimental research with pretest and posttest control and treatment groups. The population in the study were students of Tk Al – Mujahidin class A and B totaling 70 children, then divided into 2 groups; treatment and control. Pretest assessment minimum value pre test 4 and maximum value 10 with the highest mean 8.23 for the control group, while the highest Std deviation value 1.011 for the treatment group.The posttest assessment of the control group had a minimum pre-test value of 5 and a maximum value of 10 with a mean of 8.29, while the treatment group had a minimum pre-test value of 6 and a maximum value of 10 with a mean of 7.74, the highest Std deviation value was 1.292 for the treatment group. The analysis of the Mann Whitney Test it is known that there is an effect of modifying the KPSP sheet using dart games on the ability of toddlers (p value 0.012 <0.05).  From the calculation results of the Mann Whitney Test, it was concluded that there was an influence to determine the effect of modifying the KPSP sheet using the Dart game on the ability of toddlers in Al Mujahidin Kindergarten by 0.012 with a strong enough relationship strength that had a negative correlation. Thus the hypothesis was accepted (p value <0.05). Keywords: Modification, KPSP, Dart Game, Toddlers  ABSTRAK Masa balita adalah masa dikehidupan yang sangat penting dan perlu perhatian serius karena terjadi proses tumbuh kembang yang sangat pesat. Salah satu indikator penting yang mempengaruhi tumbuh kembang anak adalah status gizi. Monitoring terpenting dalam perkembangan anak ada pada 3 tahun pertama. Monitoring dapat menggunakan kuesioner pra screening perkembangan (KPSP). Kuesioner KPSP dapat di implementasikan pada anak usia 0 hingga usia 6 tahun. Tenaga Kesehatan yang dapat memantau KPSP salah satunya adalah Bidan. penelitian ini bertujuan untuk mengetahui pengaruh modifikasi lembar KPSP menggunakan dart game terhadap kemampuan balita. Penelitian ini merupakan penelitian eksperimen semu dengan rancangan pretest dan posttest kelompok kontrol dan perlakuan. Populasi dalam penelitian yaitu murid Tk Al – Mujahidin kelas A dan B berjumlah 70 anak, kemudian dibagi menjadi 2 kelompok; perlakuan dan kontrol. Penilaian pretest nilai minimal pre test 4 dan nilai maksimal 10 dengan mean tertinggi 8.23 untuk kelompok control, sedangkan nilai Std. deviation tertinggi 1.011 untuk kelompok perlakuan. Penilaian posttest kelompok kontrol nilai minimal pre test 5 dan nilai maksimal 10 dengan mean 8.29, sedangkan kelompok perlakuan nilai minimal pre test 6 dan nilai maksimal 10 dengan mean 7.74, nilai Std. deviation tertinggi 1,292 untuk nya kelompok perlakuan. Dengan menggunakan analisis Mann Whitney Test diketahui bahwa terdapat pengaruh modifikasi lembar KPSP menggunakan dart game terhadap kemampuan balita (p value 0.012 < 0.05). Dari hasil penghitungan Mann Whitney Test disimpulkan terdapat pengaruh untuk mengetahui pengaruh modifikasi lembar KPSP menggunakan Dart game terhadap kemampuan balita di TK Al Mujahidin sebesar 0.012 dengan kekuatan hubungan cukup kuat yang  berkorelasi negatif. Dengan demikian hipotesis diterima (p value < 0,05). Kata Kunci: Modifikasi, Lembar KPSP, Dart Game, Balita